Should small exporting technology enterprises use niche, strategic alliances, or both?. (1st January 2014) - Gongming, Qian; Marcus, Alexander; Lee, Li
This study compares and evaluates the niche strategy as well as the alliance strategy for small exporting technology enterprises (SETEs). The literature indicates that either strategy is effective, as both serve the same purpose of relaxing resource constraints. However, the results of this study indicate that SETEs that adopt both strategies simultaneously perform significantly better than those that adopt only one strategy so one strategy does not duplicate the other. Moreover, SETEs cannot maximise returns either if they rely heavily on both strategies simultaneously. The optimal strategy for SETEs lies either on the combination of high level of niches and low level of alliances or on the combination of low level of niches and high level of alliances.